ANALISIS MANAJEMEN SMK NEGRI 43 JAKARTA - Moh Fariz Dzikrul Kholik; Annisa Farhana; Matnur Ritonga (Jurnal Ilmiah Hospitality, 2022)
This article is the result of research that aims to find out how management aspects are carried out in SMKN 43 Jakarta schools. This study used qualitative research with the case study method and the data collection techniques used were: Observation, Interview, and Documentation. These management aspects consist 1) Curriculum Management 2) Student Management 3) management of educators and teaching staff 4) Public relations management 5) administrative management 6) facilities and infrastructure management. With this research, it explains that 1) In curriculum management the independent curriculum is carried out with this in mind, it is hoped that students will have creative and innovative talents 2) In this PPDB it is already good providing services every year the number of students increases 3) Management makes staff professional and responsible education 4) The community provides services and carries out good cooperative relations 5) In administrative management it is found that administrative management and regarding training for educators are good 6) In the management of facilities and infrastructure all facilities are fulfilled capable of making learning run comfortable. However, it is still necessary to make improvements in several aspects of planning so that everything is by existing targets and management.